A COMPARATION OF DISTINCT ELEMENT METHOD AND ANALYTICAL METHOD IN CIRCULAR TUNNEL CAUSED BY DISTANCE DEPTH - NURHAMDA (NIM : 1210 4044); Pembimbing : Prof. Dr. Ir. Irwandy Arif, MSc., SUKMAWAN
In underground mines, there are three important works of the underground mining process, these are: the creation of the entrance to the mine workers and equipment, extracting ore from the rock mass and the transport of ore to the surface. To support all these activities required the excavation underground opening. This research will be made a circular tunnel with a depth from the surface of 50 m, 100 m, 150 m, 200 m, 500 m and 1000 m. Then we analyze the displacement and stress values using the software UDEC (Universal distinct element code) and then we compare with the result from analytical method. The calculation using UDEC software will give you the results: • The results of displacement calculations using distinct element method has a average difference of 7,84% on the horizontal displacement and 9.2% on the vertical displacement compared to the results of calculations from the analytical method. • The results of principal stresses using distinct element methods has a average difference of 3,2% on major prinsipal stress and 5,93% on minor prinsipal stress compared to the results of calculations from the analytical method. • Distribution of tensile stress that is created will be more and more with the increasing depth of the hole openings. • At the tunnel wall, the increasing depth of the hole opening, thedirection of displacement will rotate from directed inside to the outside of tunnel. • The results of comparative calculations using geometric 30D will be closer to the results of analytical calculations than using geometry 20D, 10D, and 5D.